Effects of melengestrol acetate supplementation after fixed-timed artificial insemination on pregnancy rates of Bos indicus beef cows - Junior, W.M. Costa [UNESP]; Cooke, R. F.; Pereira, M. H.C. [UNESP]; Vasconcelos, J. L.M. [UNESP] (Elsevier, 2017)
This experiment compared pregnancy rates in Bos indicus cows assigned to temporary calf weaning (TCW) or eCG administration during estrus synchronization, with or without melengestrol acetate (MGA) supplementation after artificial insemination (AI). A total of 3042 lactating, multiparous, non-pregnant Nelore cows were managed in 48 groups, and assigned to an estrus synchronization + fixed-time AI protocol (d −11 to 0, with AI on d 0). On d −11, groups were randomly assigned to receive 1 of 2 gonadotropic stimulus, which were either 48-h TCW from d −2 to AI (n = 9 groups, 604 cows) or 300 IU i.m. injection of eCG on d −2 (n = 39 groups, 2438 cows). On d 1, groups were assigned to receive, in a 2 × 3 factorial arrangement, 1 of 3 MGA treatments: 0.5 mg of MGA/cow from d 5–18 (M5to18; n = 16 groups, 1074 cows) or from d 13–18 (M13to18; n = 16 groups, 971 cows), or no MGA supplementation (CON; n = 16 groups, 997 cows). Estrus expression was evaluated by painting the tailhead of each cow on d −2, and evaluating the presence of tailhead paint at AI. Body condition score (BCS; 1–9 scale) was recorded at AI, and cows were classified as adequate (≥ 4.5) or inadequate (< 4.5) BCS. Pregnancy rates on d 30 and 80 were greater (P ≤ 0.05) in M5to18 and M13to18 compared with CON cows (62.9%, 62.9%, and 55.3% on d 30, 58.1%, 59.2%, and 50.5% on d 80, respectively; SEM = 3.1), and similar (P ≥ 0.79) between M5to18 and M13to18 cows. Pregnancy rates on d 30 and 80 were similar (P ≥ 0.17) between cows assigned to eCG and TCW (58.1% and 62.6% on d 30, 54.3% and 57.6% on d 80, respectively; SEM = 2.7). The MGA supplementation × gonadotropic stimulus interaction was not significant (P ≥ 0.41) whereas no interactions of main treatment effects with cow BCS and estrus expression were detected (P ≥ 0.21) for pregnancy outcomes. Hence, supplementing B indicus beef cows with MGA post-AI increased pregnancy rates compared with non-supplemented cows, and this outcome was independent of period and length of MGA supplementation, gonadotropic stimulus, cow BCS status, and estrus expression during the synchronization protocol.
Keywords: Artificial insemination; Beef cows; Melengestrol acetate; Pregnancy rate